Low-frequency dual reversible model of the single-phase two-winding transformer considering the gradually quicker saturation process of the core. (February 2021) - Duan, Pan; Yang, Ming; Liu, Yonglai; Zou, Binyang; Ye, Shuoyu; Sima, Wenxia
Highlights: Method for describing the gradually quicker saturation process of the transformer core; Approach to compute λ-i data points by several measured magnetizing inductances; Modified dual reversible model considering the gradually quicker saturation process; The proposed model can accurately predict the first peak of inrush current. Abstract: The major nonlinear effects in the transformer core are saturation and hysteresis, in which saturation is the predominant effect for the transients involving saturation of transformers. A detailed representation of the saturation of the core is required. However, the available methods seldom provided experimental methods to represent the transients of the two magnetizing curves of the duality-based transformer model from slight saturation to deep saturation. This paper proposes a method to retrofitting the dual reversible transformer model with the gradually quicker saturation process of the core. Methods are proposed to measure the incremental inductances of the saturated core and using them to compute flux–current data of magnetizing branches of the proposed dual reversible π model. The entire magnetization curve is obtained by combining the unsaturated region by the available methods with the saturated region determined using the proposed methods. A single-phase two-winding transformer with a rated capacity of 500 VA is used to perform the proposed method to extract the required parameters of the proposed dual reversible transformer model. Inrush current tests are carried out and compared with simulations using ATP-EMTP to validate the model. Results show that the proposed model has better accuracy to simulate the first peak of the inrush current compared with the available model, contributing to the simulation involving low-frequency electromagnetic transients.